(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Cirrhosis is a late stage of liver disease in which healthy liver tissue is gradually replaced by scar tissue (fibrosis). This scarring blocks the flow of blood through the liver and impairs its ability to function properly. The liver plays a critical role in detoxifying harmful substances, producing proteins important for blood clotting, and processing nutrients, so when cirrhosis develops, these functions are compromised.